Potentiometric Study of the Biligand 1 : 1 : 1 Ln(III)-CDTA-Valine/Leucine/Serine Complexes and Evaluation of Thermodynamic Parameters - Kaurav, M.S.; Gaur, Gajendra; Singh, B.P. (Asian Journal of Chemistry, 2010)
Ternary 1 : 1 : 1 Ln(III)-L-L´ complexes have been investigated by potentiometric titration method [Ln(III) = Tb(III), Dy(III), Ho(III) and Er(III), L = cyclohexane diamine N,N,N´,N´- tetraacetic acid and L’ = valine, leucine and serine]. The stability constants of these ligands together with thermodynamic parameters. viz., free energy of formation ΔG, enthalpy change ΔH and entropy change ΔS at different ionic strengths (μ = 0.05, 0.10 and 0.15 M KNO3) and varying temperatures, i.e., 25, 35 and 45ºC, have been investigated. Relative order of stabilities observed as Tb(III) <Dy(III) < HO(III) < Er(III).